European Union Copyright Law and Gaming Video Content : Obstacles and Opportunities for Online User Creativity - Melart, Samuli (fi=Turun yliopisto|en=University of Turku|, 2017)
This thesis studies gaming video content from the perspective of the exceptions and limitations to copyright in the European Union. More specifically, it analyses whether the current exceptions and limitations are capable of accommodating transformative uses of video game content. Further, by studying how the game industry has reacted to gaming videos in their licensing practices, this thesis seeks to find new approaches that could benefit the future efforts to amend the copyright framework of the Union. For those purposes, this thesis utilizes legal dogmatic and law and economics methodologies combined with a critical approach Gaming videos have become one of the most popular forms of user-generated content, in which people innovatively use video games to create video content that spans from humorous expressions to records of competitive gaming. Yet, majority of gaming videos do not benefit from the current exceptions and limitations under Directive 2001/29. Gaming videos are able to flourish mainly due to considerably wide approval of the game industry. This thesis concludes that the EU copyright law is in its current state unreasonably biased for the rightholders and does not provide necessary elasticity to accommodate gaming video content through its current copyright exceptions and limitations. The most appropriate mean to amend the deficiencies would be to introduce a specific user-generated content exception based on the Canadian model. Gaming video licensing practices exemplify how to establish workable solutions for effective remuneration schemes and clarify the concept of commercial use.